Genetic diversity and spread of recombinant coxsackievirus A4 in hand, foot, and mouth disease cases in Bangkok, Thailand: 2017–2023 - Jiratchaya Puenpa; Sumeth Korkong; Preeyaporn Vichaiwattana; Yong Poovorawan (Scientific Reports)
Abstract Coxsackievirus A4 (CVA4) has recently become one of the most common causative agents of hand, foot, and mouth disease. The current study investigated the genetic diversity and spread of recombinant CVA4 by analyzing circulating genotypes and recombinant strains in Bangkok, Thailand, from 2017 to 2023. Partial VP1, 3Dpol, and whole genome sequencing of CVA4 samples collected from collaborating hospitals were conducted. Phylogenetic analysis of CVA4 VP1 and 3Dpol genome regions revealed discordance, indicating recombination. The predominant CVA4 genotype was C3, primarily observed in 2019. The predominant genotype in 2017 was C1. D2, commonly found in China, was occasionally observed. In nucleotide similarity analysis, intertypic recombination between CVA4 and EV-A during the evolutionary history of the virus was evident, particularly in the nonstructural region. The estimated emergence of genotypes C1 and C3 in Thailand occurred around 2014, with an evolutionary rate of 5.8 × 10− 3 nucleotide substitutions per site per year. Genotype D2 exhibited notable variability across both the entire genome and the structural protein region compared to genotype C. Monitoring the genetic diversity and circulation of recombinant CVA4 is crucial for identifying newly emerging virus strains, enabling prompt public health responses and containment efforts, and enhancing surveillance in Thailand.